The joint Maghreb struggle in the literature of the National Liberation Front and the Moroccan Independence Party 1954-1956 - Merdji , Abdelhalim (Journal of Social Sciences and Humanities, 2023)
The local, regional and international circumstances, especially the presence of the French occupation in the Algerian country and the rest of the countries of the Maghreb region, was practicing its arbitrary policies and persecution of the inhabitants of the region, especially the Algerian people, who were living these practices in their various arbitrary and criminal forms. N in the Maghreb political arena through their liberation struggle against colonialism and its arbitrary policies against the people of the Maghreb, like other liberation movements, in finding a common Maghreb revolutionary struggle against colonialism. This study aims to highlight the extent of the interests of the National Liberation Front and the Istiqlal Party in the issue of the joint Maghreb struggle between 1954 AD and 1956 AD by highlighting those different positions on the issue of the outbreak of the Algerian liberation revolution and then reviewing the positions of the Istiqlal Party, and the extent of its interests on the issue of coordination of the joint Maghreb action, in turn addressing To the fate of the issue of the common Moroccan sword, especially in light of the independence of Tunisia and Morocco, and the survival of Algeria under the leadership of the National Liberation Front alone in the face of French colonialism and its arbitrary and barbaric policies until 1962 AD.